FAKTOR–FAKTOR YANG MEMPENGARUHI PEMILIHAN METODE PENILAIAN PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Imay Sulistiyani, 14.05.62.0015; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze the factors that influence the selection of inventory valuation methods in manufacturing companies listed on the Indonesia Stock Exchange. In this study there are 5 dependent variables including financial leverage, company size, managerial ownership, current ratio and inventory variability. While the independent variables are inventory valuation methods namely FIFO and average. The sampling method uses purposive sampling method with the study period of 2015 to 2017. The data used in this study is secondary data. The number of samples used is 222 data and research testing uses logistic regression analysis method. The results of this study indicate that the variables of firm sizeinfluence the selection of inventory valuation methods. Then variable financial leverage,managerial ownership, current ratio and inventory variability do not affectthe selection ofinventory valuation methods. Keywords: Financial Leverage, Company Size, Managerial Ownership, CurrentRatio, Inventory Variability and Inventory Assessment Method.